(untitled) (Pravaha, 2021)
Service quality is important assessment through which overall service dimension can be conformed to the client’s expectations. The main purpose of this study is to examine impact of service quality on customer loyalty with the mediating effect of customer satisfaction. In order to collect data for analysis, 154 completely filled online questionnaires were collected. Four stepped method suggested by Baron and Kenny (1986) was used for examination of mediating effect of customer satisfaction. After testing the hypotheses using various techniques, it was found that service quality has significant positive impact on customer satisfaction and customer loyalty. The customer satisfaction partially mediates between service quality and customer loyalty. This research is useful for commercial banks so that they can improve service quality to the customers and thus maintain customer satisfaction and loyalty. Similarly, the policy makers can also use this finding while formulating future plans in banking sector.